Relative bioavailability of salbutamol to the lung following inhalation when administration is prolonged - Silkstone, V L (Blackwell Science Inc, 2000)
AIMS: Urinary salbutamol post‐inhalation has been shown to be an index of lung deposition. The possibility of using the urinary method for prolonged periods of inhalation (such as nebulized therapy) has been evaluated. METHODS: On separate study days volunteers received salbutamol 5 × 100 µg via either oral administration (ORAL), oral with 5 g oral charcoal (ORAL + C), inhaled from a metered dose inhaler (MDI) or MDI plus 5 g oral charcoal (MDI + C). Each dose was separated by 2 min, i.e. administration time of 8 min. Urine samples were provided at 0, 30, 40, 60 and 120 min postdose. Also seven subjects inhaled 5×100 µg doses from the MDI on five separate occasions and provided urine 0–30 min post dose. RESULTS: No salbutamol was detected in urine samples following ORAL + C. The mean (s.d.) amounts of salbutamol excreted in the urine in the first 30 min post ORAL, MDI and MDI + C were 0.42 (0.55), 11.01 (3.77) and 11.60 (3.68) µg, respectively. The ratio of urinary salbutamol following MDI and MDI + C to ORAL in the 0–30 min collection period was 26.2 and 27.8, and between 30 and 40 min postdose was 5.1 and 4.7, respectively. There was no difference between urinary salbutamol over the first 30 min following MDI and MDI + C with a mean ratio (90% confidence interval) of 95.6 (84.0, 107.2). The mean (s.d.) coefficient of variation for the 30 min urinary salbutamol elimination following inhalation of 5 × 100 µg doses from the MDI by seven subjects (on 5 separate study days) was 9.4 (2.3) %. CONCLUSIONS: The 30 min urinary salbutamol method can be used for an inhalation period of up to 8 min to identify the relative bioavailability to the lung. Samples taken after this time period are affected by excretion of the oral absorbed fraction. Most nebulisers deliver their dose within this administration time.